Gambaran Kecemasan Pendamping Pasien Hemodialisa di Masa Pandemi COVID-19 Tahun 2020 - Nimsi Melati; Agustin Eka Kristiningsih; Eko Widayanto; Eni Purwanti; Maretha Windriyana (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The current COVID-19 pandemic has had a huge impact on everyone. One of the affected parties is the companion of hemodialysis patients. The patient's companion feels anxious if he or his family is infected in the hemodialysis room. This study aims to determine the anxiety description of hemodialysis patient companions during the COVID-19 pandemic. This type of research was descriptive quantitative with an online survey method. The research subjects were 100 companions of hemodialysis patients at hemodialysis centers throughout Indonesia, selected by accidental sampling technique. Data on anxiety levels were collected through filling out the Zung self rating anxiety scale (ZRAS) questionnaire which had been adapted. The results showed that most of the patient companions did not experience anxiety 98 respondents (98%) and 2 respondents (2%) experienced mild to moderate anxiety. The results of this study can be a reference for hospitals that have hemodialysis units to provide more support to hemodialysis patient companions so they don't feel anxiety and can provide good assistance.Keywords: COVID-19; anxiety; patient; patient companionABSTRAK Masa pandemi COVID-19 saat ini memberikan dampak yang besar bagi semua orang. Salah pihak yang terdampak adalah pendamping pasien hemodialisa. Pendamping pasien merasa cemas jika dirinya atau keluarganya tertular di dalam ruang hemodialisa. Penelitian ini bertujuan untuk mengetahui gambaran kecemasan pendamping pasien hemodialisa di masa pandemi COVID-19. Jenis peneltian ini adalah deskriptif kuantitatif dengan metode survei secara online. Subjek penelitian adalah 100 pendamping pasien hemodialisa di pusat hemodialisa di seluruh Indonesia, yang dipilih dengan teknik accidental sampling. Data tentang tingkat kecemasan dikumpulkan melalui pengisian kuesioner Zung self rating anxiety scale (ZRAS) yang telah diadaptasi. Hasil penelitian menunjukkan bahwa sebagian besar pendamping pasien tidak mengalami kecemasan 98 responden (98%) dan 2 responden (2%) mengalami kecemasan ringan sampai sedang. Hasil penelitian ini dapat menjadi acuan bagi rumah sakit yang memiliki unit hemodialisa untuk memberikan dukungan yang lebih kepada pendamping pasien hemodialisa agar tidak merasakan kecemasan dan dapat melakukan pendampingan dengan baik.Kata kunci: COVID-19; kecemasan; pasien; pendamping pasien